2017
DOI: 10.1200/jco.2017.74.5471
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Efficacy of Pembrolizumab in Advanced, Programmed Death Ligand 1–Positive Cervical Cancer: Results From the Phase Ib KEYNOTE-028 Trial

Abstract: Purpose The KEYNOTE-028 trial ( ClinicalTrials.gov identifier: NCT02054806) was designed to assess the safety and efficacy of pembrolizumab in 20 programmed death ligand 1-positive, advanced solid tumor cohorts. Here, we present the results from the cohort of patients with advanced cervical cancer. Methods Patients were treated with pembrolizumab 10 mg/kg every 2 weeks for up to 24 months. Response was assessed every 8 weeks for the first 6 months and every 12 weeks thereafter. The primary end point was overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
314
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(357 citation statements)
references
References 30 publications
6
314
3
3
Order By: Relevance
“…The majority of these patients had progressed on first -line therapy. 25 Likewise, the KEYNOTE-028 and KEYNOTE-158 trials 26,27 reported on more than 100 patients with programmed death ligand 1Yexpressing recurrent cervical cancer, all of whom had had prior treatment for advanced disease. Treatment with pembrolizumab led to an overall RRs of~15%, with an addi-tional~15% experiencing SD.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these patients had progressed on first -line therapy. 25 Likewise, the KEYNOTE-028 and KEYNOTE-158 trials 26,27 reported on more than 100 patients with programmed death ligand 1Yexpressing recurrent cervical cancer, all of whom had had prior treatment for advanced disease. Treatment with pembrolizumab led to an overall RRs of~15%, with an addi-tional~15% experiencing SD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the KEYNOTE-028 and Checkmate 358 study, we treated patients irrespective of overexpression of PD-L1 and found similar response rates. 10,14 This is not surprising because the accuracy of PD-L1 expression in predicting treatment response remains controversial. The PD-L1 expression analysis is still an area of active study, and varying results have been reported with different antibodies, staining platforms, and scoring criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A tumor proportion score of more than 1% was considered positive based on previous studies. 9,10 A baseline computed tomography (CT) scan was performed, and primary target lesions were identified and measured. Clinicopathological data at initial diagnosis and at time of last recurrence were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Pembrolizumab has rarely been utilized in the gynecologic setting; however, it has been reported to have a favorable safety profile and durable antitumor activity in cervical and endometrial cancer [39][40][41] as well as gestational trophoblastic neoplasia [42]. Several toxicities have been encountered with pembrolizumab such as fatigue, nausea, myalgia, arthralgia, and colitis [31,35,37].…”
Section: Discussionmentioning
confidence: 99%